Cross-layerly embedded FBG in carbon fiber composites for self-modulated, intensity referenced and temperature insensitive microdisplacement measurement - Dong, Bo; Xiao, Long; Gong, Yandong; Wang, Yixin (Sensors and actuators. A. Physical., 2013)
•A novel packaging structure with an FBG cross-layerly embedded in carbon fiber composites.•It is selfmodulated and intensity referenced.•It is temperature insensitive.•It has good reproducibility. A novel temperature insensitive and intensity modulated microdisplacement sensor is demonstrated by cross-layerly embedding an FBG in carbon fiber composites. The reflection spectrum of the FBG is selfmodulated to be chirped spectrum if a microdisplacement is applied to the center of the sensor structure. By monitoring the optical power change due to the above chirped spectrum variation, the microdisplacement can be measured. Experimental results show that there are quasilinear relationships between the microdisplacement and optical power, the maximum measurement resolution of the sensor reaches 10.7μm within the displacement range of 0–1050μm, and the dynamic measurement range is within the range of 0–200Hz.